The Understanding Mathematical Communication Concepts and Skills: Analysis of the Ability of Prospective Physics Teachers? - Yusuf, Irfan; Zb, Aminah; Rozal, Edi (International Journal of Education and Teaching Zone, 2022)
The research that has been carried out aims to see the ability to understand mathematical concepts and mathematical communication of students on the Maxwell-Boltzman material for Tadris Physics students, especially students in semester VI. This research is a quantitative descriptive study in which the data collected from the test results and the results of the lecture process at the time of giving the Maxwell-Boltzman material will be analyzed and described and added with a test technique on the cognitive domain in the form of a description test (essay) consisting of 7 test questions, where five questions are for understanding students' mathematical concepts and two questions for technical analysis of students' mathematical communication skills. The data obtained in the quantitative analysis and according to the five categories that have been determined. The facts obtained from the results of the study show that students' ability to understand mathematical concepts in the Maxwell-Boltzman material is in the Good Enough category, and the average mathematical communication ability of students is also in the Good Enough category.